UMKM DIGITALISATION: A BRIDGE TO ECONOMIC INCLUSION IN THE DIGITAL ECONOMY LANDSCAPE - Lucky Mahesa Yahya; Melyana R Pugu (Adisam Publisher, 2025)
Digitalisation of MSMEs plays an important role in promoting economic inclusion in the digital era. This study aims to analyse the potential and challenges of MSME digitalisation, and identify strategies to realise this potential. The method used is a literature study. The results show that digitalisation can help MSMEs expand market access, improve efficiency, and create new business opportunities. However, MSMEs also face various challenges, such as the digital divide, lack of digital literacy, and limited access to resources. To overcome these challenges, collaboration between the government, private sector, and community is needed to create an ecosystem conducive to MSME digitalisation. Recommended strategies include providing digital infrastructure, improving digital literacy, access to finance and resources, as well as regulations that support innovation and data protection. With an inclusive and comprehensive approach, digitalisation of MSMEs can contribute to poverty alleviation, reduction of economic disparities, and sustainable economic development.